2017
DOI: 10.1007/s40094-017-0243-2
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of highly hydrophobic Mn nano-sculptured thin films and evaluation of surface properties on hydrophobicity

Abstract: The wettability of solid surfaces is important from the aspects of both science and technology. The Mn nano-sculptured thin films were designed and fabricated by oblique angle deposition of Mn on glass substrates at room temperature. The obtained structure was characterized by field emission scanning electron microscopy and atomic force microscopy. The wettability of thin films samples was investigated by water contact angle (WCA). The 4-pointed helical star-shaped structure exhibits hydrophobicity with static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…It occurs in the case of an external force, such as pressure or vibration applied to the liquid. It is reported that increasing Laplace pressure induced this transition [63]. Additionally, altering of surface roughness or increasing such as structure's holes depth, making the shift from Cassie-Baster state to Wenzel state easier [167,168].…”
Section: Transition Between Wenzel and Cassie-baxter Statesmentioning
confidence: 92%
See 2 more Smart Citations
“…It occurs in the case of an external force, such as pressure or vibration applied to the liquid. It is reported that increasing Laplace pressure induced this transition [63]. Additionally, altering of surface roughness or increasing such as structure's holes depth, making the shift from Cassie-Baster state to Wenzel state easier [167,168].…”
Section: Transition Between Wenzel and Cassie-baxter Statesmentioning
confidence: 92%
“…The wettability of surfaces can be evaluated by measuring the contact angle (CA) of a liquid on a surface and its surface tension, which is described by Young's equation. Between the solid/liquid interface, the droplet can be flattened or rolled off according to the degree of contact angle value (from 0° to 180°) [60][61][62][63].…”
Section: Chapter ⅱ Literature Review 21 Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation